2019
DOI: 10.1177/0091217419837071
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and attachment among women hospitalized on an antepartum unit

Abstract: Objective To examine the prevalence of depression, anxiety, attachment issues, and associated factors among pregnant women hospitalized on an antepartum unit. Method Ninety-eight women hospitalized on an antepartum unit reported demographic and social information and were evaluated with screening tools for depression, anxiety, and maternal–fetal attachment. Data were analyzed using descriptive statistics and logistical regression analysis. Results Over one third (36%) of participants screened at risk for depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 27 publications
1
40
0
2
Order By: Relevance
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the 45 studies included in the current review, 31 found a negative association between prenatal attachment and perinatal depression [22,74,75,81,84,86,[89][90][91][92]95,[97][98][99]101,102,[104][105][106][107][108][110][111][112][114][115][116][117][118][119][120], while a positive relation between perinatal depression and some dimensions of antenatal attachment was identified in three studies [94,102,106]. Thirteen studies did not highlight significant associations between these variables [76,[78][79][80]85,87,88,93,96,100,103,109,113].…”
Section: Main Findingsmentioning
confidence: 99%
See 3 more Smart Citations